Dragones, Creatividad y Generación de Conocimiento (2013)
This article shows, from an alternative optic to understanding the Law, a proposal, wich analyzes the fundamental issues of legal research, especially in the Faculty of Law of the Santo Tomás University, that is characterized by his modular system.